Educational Value of Johan Vincent Galtung's Conflict Resolution in Reducing Gender Issues Based Violence - Dodi, Limas (Didaktika Religia, 2018)
This article will explore the educational value of Johan Vincent Galtung's thoughts on conflict resolution that he offers in breaking down gender-based violence. As many people already know that gender issues are very closely related to discussions about violence. Apart from direct violence, Galtung emphasized another form of violence, namely structural violence, which was not carried out by individuals but hidden in smaller and wider structures. Penetration, segmentation, marginalization and fragmentation, as part of exploitation are reinforcing components in structures that function to block formation and mobility from struggling against exploitation. Johan Galtung's thinking is in line with the thinking of radical feminists. Galtung claims patriarchy as direct, structural and cultural violence. Patriarchy creates a dichotomy between public and private roles, productive and reproductive, which forms an unequal power relations between men and women. As a peace activist, the educational value of conflict resolution offered by Galtung was considered quite wise. Violence is not only done by men, but also by women. According to him, what should be hated is patriarchy, not men. Various forms of violence can be eradicated and replaced with peace. If everyone agrees not to commit physical violence, in which there is gender based violence, then everyone will also get peace.